Scaling service delivery in a failed state: cocoa smallholders, Farmer Field Schools, persistent bureaucrats and institutional work in Côte d’Ivoire - Muilerman, Sander; Vellema, Sietze R. (Informa UK Limited, 2017)
The increased use of sustainability standards in the international trade in cocoa challenges companies to find effective modes of service delivery to large numbers of small-scale farmers. A case study of the Sustainable Tree Crops Program targeting the small-scale cocoa producers in Côte d’Ivoire supplying international commodity markets shifts attention from mechanisms of private governance to the embedding of service delivery in the institutional dynamics of the state. It demonstrates that, despite a recent history of violent conflict and civil unrest, the introduced Farmer Field Schools programme achieved a surprising scale in terms of numbers and geographical spread. The analysis of this outcome combines political science and anthropological studies of effective and developmental elements in the state with the interest in institutional work found in organization science. The scaling of a new form of service delivery is explained by the skillful practices of institutional work by managers of a public–private partnership. They have been professionally associated with the sector for a long time and had the capacity to embed new forms of service delivery in persistent pockets of bureaucratic effectiveness in a failed state.